The Challenges of Protecting Refugees in Mixed Migration, vis-à-vis the Application of Articles 1f and 31 of the Refugee Convention - Eberechi, Oghenerioborue Esther (Obiter, 2020)
This article embarks on a critical analysis of the application of articles 1F and 31 of the Refugee Convention in a mixed migration setting in Africa. It exposes the problem of mixed migration and how it affects refugees and offers a brief history and scope and purpose of these articles. This study argues that article 1F(b) is ambiguous and inadequate, and that it provides room for adjudicators to exclude certain migrants from refugee status. On the other hand, owing to vagueness in these articles, refugees can be penalised, criminalised and detained for possible extradition and repatriation. Additionally, refugees who enter countries of refuge amidst other migrants may find it difficult to report to an appropriate centre to apply for refugee status. Thus, they are not able to comply with article 31 of the Refugee Convention. Therefore, the author recommends the amendment of both articles 1F and 31 of the Refugee Convention to eliminate problematic ambiguities.